Pengaruh Penggantian Rumput Gajah (Pennisetum purpureum) dengan Rumput Kumpai (Hymenachne amplixicaulis ) Terhadap Kecernaan Bahan Kering & Bahan Organik dan Konsumsi Air Minum Domba Lokal Jantan - Nasution, Ahmad (Fakultas Peternakan Universitas Jambi, 2009)
The experiment was conducted to know the effect of elephan grass substitution with kumpai grass according to dry matter, organic matter digestibility and water consumption ofÂ local young male lamb. Three local young male lamb post weaning with body weight 5 kg, 6,5 kg and 7,5 kg respectively were arrange to latin square design experiment. The treatments were R0 94 % elephan grass, R1 94 % fresh kumpai grass and R2 94 % kumpai grass hay andÂ 6 % of rice bran was also added to each treatment. The result showed that the substitution of elephan grass with fresh kumpai grass did not affect thedigestibility of dry matter or organic matter. Meanwhile the water consumption was significantly higher for third treatment compared to the other treatments. From the result we can conclude that the quality of fresh kumpai grass and elephan grass was approximately equal according to dray matter and organic matter digestibility, but water consumption was affected by the water persentage in ration. Â